(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
Taking into account the loss of stability of slopes, as well as the results of theoretical and experimental studies of landslide phenomena, the role of microorganisms in the process of reducing the stability of soils of landslide slopes and the issue of activation of landslide phenomena is considered.